A Non-invasive Method to Evaluate the Efficacy of Human Myoblast in Botulinum-A Toxin Induced Stress Urinary Incontinence Model in Rats - Bandyopadhyay, Balaji; Thakur, Anirban; Dave, Viral; Viswanathan, Chandra; Ghosh, Deepa (Urology Journal, 2014)
Abstract Purpose: To develop a simple non-invasive method to assess the efficacy of a cell based therapy for treating stress urinary incontinence (SUI). Materials and Methods: In this study, skeletal myoblasts were used as candidate therapy to reverse SUI. The SUI model was created in rats using periurethral injection of botulinum-A toxin injection. Two weeks later, the rats were administered saline and the level of continence in each botulinum-A toxin treated and control animals was assessed by the extent of voiding using metabolic cages. To determine the efficacy of myoblasts to reverse SUI, botulinum-A toxin treated incontinent rats were injected with either cultured human skeletal myoblasts or with buffered saline (sham control). Two weeks post implantation, the extent of continence was evaluated as mentioned above. Results: The difference in void volume between botulinum-A toxin -treated and control rats were significant. Histological analysis of the urethra showed remarkable atrophy of the muscular layer. A significant reversal (P = .025) in the volume of voiding was observed in cell-implanted rats as compared to sham injected rats. Histological analysis of the urethra implanted with myoblasts showed recovery of the atrophied muscular layer in comparison to sham control. Immunofluorescence analysis of the cell injected tissues confirmed the presence of human myoblasts in the regenerated area. Conclusion: This simplified method of in vivo testing can serve as a tool to test the efficacy of new therapies for treating SUI.